Physiological Effect of Seasonal Variations with Special Reference to Different Daihik Prakriti - Singh, Ajit; Dubey, Sushil (Journal of Neonatal Surgery, 2025)
Background : Ayurveda - "science of life and longevity" is considered as the traditional system of medicine of India. It is the oldest health care system on the earth. It is holistic & qualitative science of health and longevity, which include person as a whole, body and mind. The aim of this system is to prevent illness, heal the sick and preserve life. Since origin of Ayurveda, philosophy and medicine were not separated. Therefore, philosophical views have strongly incorporated in the Ayurvedic way of thinking. Nine matters (dravya) has been described in Ayurveda [panchmahabhuta (5 basic elements), aatma (soul), mana (psyche), kala (time) and disha (direction)]. They all have close relationship with body. Methods: Prakriti of the subjects were determined by the proforma as described in various classics of Ayurveda (Annexure no.II) and were categorized into 1.Vataja (vata-pittaja and vata-kaphaja), 2. Pittaja (pitta-vataja and pitta-kaphaja) and 3.Kaphaja (kapha-vataja and kapha-pittaja) prakriti. The volunteers were provided detailed information about purpose and methods used in the study, before written consent was obtained. Results: On the basis of above mentioned facts as observed by the investigator that seasons have different level of impact on our body in different types of the prakriti (personality) persons. In last we can conclude that day and night (dincharya), and seasonal regime (ritucharya) should be followed for maintenance of healthy life and doses of different drugs may also be determined as per seasons and their prakriti in different diseases. Conclusions: The most important principle of Ayurvedic system of medicine is preventive aspect, which can be achieved by the minor change in diet and life style activities in response to change in season. This is a very important aspect of prevention of diseases by maintaining the physiological activities in our body